2003
DOI: 10.1080/0957514032000045564
|View full text |Cite
|
Sign up to set email alerts
|

"I Didn't Expect That I Would Get Tons of Friends More Each Day": Children's experiences of friendship during the transition to school

Abstract: This article presents some of the findings from a study that explores the complex nature of the transition to school, and looks specifically at 23 children's experiences of friendship and the way in which this impacted on their early experiences of school. Observations of the children, and interviews with the children, their families and their teachers, revealed that not only did friends play a vital role in facilitating the children's transition to formal schooling, they also assisted directly in facilitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 6 publications
4
40
0
1
Order By: Relevance
“…The results of the project indicated that friendships were strongly emphasised by the children at all stages of the transition. This supports previous literature that stresses the importance of friendships for all children entering into formal schooling (Jackson 2010, Peters, 2003, Fisher, 2009). However, much of the existing literature concerning newly arrived children transitioning into mainstream classes indicate that these students are likely to face additional social vulnerability (Correa-Velez et al, 2010), and in the current study this was evident in participants' concerns around making friends, together with the comfort provided by the knowledge that a friend was transitioning alongside them.…”
Section: Notions Of Ethnicity Amongst Students Newly Arrived To Austrsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of the project indicated that friendships were strongly emphasised by the children at all stages of the transition. This supports previous literature that stresses the importance of friendships for all children entering into formal schooling (Jackson 2010, Peters, 2003, Fisher, 2009). However, much of the existing literature concerning newly arrived children transitioning into mainstream classes indicate that these students are likely to face additional social vulnerability (Correa-Velez et al, 2010), and in the current study this was evident in participants' concerns around making friends, together with the comfort provided by the knowledge that a friend was transitioning alongside them.…”
Section: Notions Of Ethnicity Amongst Students Newly Arrived To Austrsupporting
confidence: 80%
“…These findings reiterate the importance of social networks and friendships in the transitions of children into school (Boulton et al, 2011;Hek, 2005;Peters, 2003).…”
Section: Going To School Is a Positive Experiencementioning
confidence: 86%
“…Children's views of school have been explored in a number of studies in recent years (Broström, 1995, September;Clarke & Sharpe, 2003;Corsaro & Molinari, 2005Dockett & Perry, 2003Einarsdóttir, 2003Einarsdóttir, , 2010Griebel & Niesel, 2003;Peters, 2003). In general, children report a sense of "growing up" as they make the start to school, reflecting a change in identity as they become school students.…”
Section: Children's Views Of Transition To Schoolmentioning
confidence: 99%
“…The significance that children attach to making and maintaining friendships is a frequent theme in the literature; and is the single most significant factor that children associate with positive school experiences (Dockett & Perry, 1999;Peters, 2003;Sheridan & Pramling Samuelsson, 2001). Relating to peers and developing positive relationships, having opportunity for the privacy, time and space to 'play' with 'friends', are of high priority to children; and correlate to their overall experience of school life.…”
Section: Educational Implications: Enabling Environmentsmentioning
confidence: 99%